Effect of Porogen Incorporation on Pore Morphology of Low-k SiCxNy Films Prepared Using PECVD. (1st January 2015) - Tu, Hung-En; Su, Chun-Jen; Jeng, U-Ser; Leu, Jihperng
Abstract : Low-k porous SiCx Ny films were prepared through plasma-enhanced chemical vapor deposition, using 1, 3, 5-trimethyl-1, 3, 5-trivinylcyclotrisilazane (VSZ) as the matrix precursor and epoxycyclohexane (ECH) as a porogen. The effects of porogen loading and deposition temperature on porogen incorporation, pore morphology, and the properties of porous SiCx Ny films were examined. In addition, the impact of film shrinkage and the corresponding nanopore structures after annealing were studied. The porosity of films deposited at 100°C increased from 1.8% to 19.8% when ECH loading increased to 30%, above which the porosity remained nearly constant because of high film shrinkage. The pore size decreased slightly from 4.1 to 3.7 nm when ECH loading increased to 30%, above which the pores became larger and were broadly distributed. By contrast, increasing deposition temperature at 20% ECH loading decreased porogen incorporation and increased film density. The porosities and pore size of films decreased, respectively, when the deposition temperature increased. A short-range ordering of pores was observed only at low deposition temperatures because the N-Si-C cross-linked structures and organic phase were present. Optimized processing parameters facilitated the fabrication of low-k porous SiCx Ny films exhibiting 19.8% porosity, 3.7-nm pores, a k value of 3.18, and an elastic modulus of 7.7 GPa.